Pelatihan Pendidikan Berupa Taman Belajar Bagi Anak Yayasan Panti Asuhan Sayangi Anak Kasih Hati - Citra Mutiara Nasution; Dewi Ratih; Angelica Patricia; Calvin Girsang; Siti Safitri; Fajar Utama Ritonga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
An orphanage is a social institution that has the responsibility to provide social welfare services to neglected children, as well as to provide substitute services for parents/guardians of children in meeting the physical, mental and social needs of children. Social services are very much needed for children in orphanages. especially education services, referring to the results of research showing that the fulfillment of the rights and educational needs of children in orphanages has not been maximized. Education is basically the right of every child without exception. Education functions to shape students' attitudes and orientation towards learning, instill a positive attitude and thirst for knowledge. In providing educational training to children using the fulfillment of educational needs using the group method (Group Work) this is a comprehensive education about educational training as a garden of learning. The intervention program used in this Practicum activity is the Mezzo Intervention by Zastrow which consists of; Preparation (with a Non-Directive Approach), Intake / Engagement, Assessment, Planning, Implementation and Action Plan, Evaluation and Termination.. Can increase the knowledge, skills and creativity of orphanage children. The children of the Kasih Hati Orphanage Foundation can read, write, and count well.